A Contribution to the Fauna of Raspy Crickets (Orthoptera: Gryllacrididae: Gryllacridinae) in Korea - Taewoo, Kim; Byeongmin, Jeong; Jaeil, Shim (Zootaxa, 2014)
The little known raspy cricket subfamily Gryllacridinae is reviewed for Korea. Three species are confirmed through material examination and are taxonomically considered as follows: Eugryllacris japonica (Matsumura et Shiraki, 1908) comb. nov. is transferred from Prosopogryllacris japonica (Matsumura et Shiraki, 1908), Nippancistroger testaceus (Matsumura et Shiraki, 1908) has a newly proposed junior synonym Nippancistroger koreanus Storozhenko & Paik, 2003 syn. nov., and Metriogryllacris tigris sp. nov. is newly described from the far southern Yeoseo-do Island.